"Jeg maa aldrig glemme Kierkegaard" - Den afgørende dannelseserfaring i kritikeren og samfundsrevseren Georg Brandes’ liv var Søren Kierkegarrd, hvis religiøsitet var ham fremmed - Christensen, Lars (Slagmark - Tidsskrift for idéhistorie, 2018)
Kierkegaard was perhaps the single most important influence for the internationally renowned Danish critic Georg Brandes (1842-1927). As a young student, Brandes eagerly studied and admired the Danish philosopher and theologian. Brandes, a secular Jew, saw in Kierkegaard his initiator into the Christian Faith, but he despaired over the radicalism of Kierkegaard’s demands. Brandes later turned into an ardent critic of religion, and his biography of Kierkegaard attempts to give a psychological explanation of Kierkegaard’s belief. However, he remained steeped in kierkegaardian ways of thinking, evident in his enthusiastic writing on the rebel Nietzsche.